Das “Juventudes” dos Antigos Movimentos de Libertação aos “Revús”: Diversidade identitária do ativismo político e cívico angolano, da luta armada anticolonial ao caso dos “15 +2”, 1960-2015 - Jean-Michel Mabeko-Tali (Cadernos de Estudos Africanos)
This text presents a historical-analytical framework of the different dynamics of youth politics in Angola, starting with youth supporters of the liberation movements, going through their political impact in the post-independence period and repression around the 27th of May, ending with their re-emergence in the most recent manifestations of the so-called Revús.